2021
DOI: 10.1088/1755-1315/781/4/042003
|View full text |Cite
|
Sign up to set email alerts
|

Research on Distribution Strategy of Charging Piles for Electric Vehicles

Abstract: The distribution and scale of charging piles needs to consider the power allocation and environmental adaptability of charging piles. Through the multi-objective optimization modeling, the heuristic algorithm is used to analyze the distribution strategy of charging piles in the region, and the distribution of charging piles is determined to meet the minimum consumption of charging path, and then the construction scale is determined according to the calculation of environmental fitness. The rationalization of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The transmission of inter-cluster data uses a multi-hop routing mechanism based on trust value inspiration, which improves the scalability of the algorithm. The trust value is used to characterize the degree of suitability of nodes to undertake the data forwarding task, and without considering the pseudo-data in the sensor data, model is given by the following Gaussian likelihood function: (16) Where, denotes the nd sensor.…”
Section: Sensor Cluster Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission of inter-cluster data uses a multi-hop routing mechanism based on trust value inspiration, which improves the scalability of the algorithm. The trust value is used to characterize the degree of suitability of nodes to undertake the data forwarding task, and without considering the pseudo-data in the sensor data, model is given by the following Gaussian likelihood function: (16) Where, denotes the nd sensor.…”
Section: Sensor Cluster Establishmentmentioning
confidence: 99%
“…A heuristic algorithm is employed to analyze the distribution of charging piles in the region through multi-objective optimization modeling and determine the minimum consumption that can satisfy the charging path. The construction scale is then determined based on the calculation of environmental adaptability, and the rationalization of the distribution and construction scale of charging piles can achieve an effective allocation of power distribution and transmission [16]. It has also been shown that electric vehicle charging piles have become an important green infrastructure in cities; however, only a few people have paid attention to the historical pile distribution.…”
Section: Introductionmentioning
confidence: 99%